Late quaternary paleoseismology of the Khlong Marui Fault in the Thub Pud area, Phang Nga, southern Thailand - Weerachat Wiwegwin; Passakorn Pananont; Kitti Khaowiset; Suwith Kosuwan (Songklanakarin Journal of Science and Technology (SJST), 2022)
Remote sensing and aerial photography techniques have been applied in a study of the Khlong Marui Fault in Surat Thani and Phang Nga provinces of southern Thailand. Several faults are recognized in the region, trending mainly NE–SW. The common geomorphological features associated with the Khlong Marui Fault include fault scarps, triangular facets, offset streams, shutter ridges, hot springs, and linear valleys. Paleoseismological trenching at Ban Pak Dan across the NE–SW Khao Panom segment of the Khlong Marui Fault was conducted to identify and date faulting events. Two events with magnitude (Mw) 6.9 were observed at the Ban Pak Dan trench site, and OSL dating indicate late Quaternary faulting events from 20,000 ±1,500 years ago; and from 14,500 ±1,000 years ago. The maximum slip rate is estimated to be 0.25–0.50 mm/yr, and the recurrence interval of seismic events is between 1,000 and 2,000 years.